2021
DOI: 10.31258/unricsce.3.40-46
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Teknologi Tepat Guna (E-Ox Level) kepada kelompok pembudidaya Ikan Lele di Desa Kepongpongan Kabupaten Cirebon

Abstract: Partners realize that the production of cultivated fish can still be increased, one of which is by monitoring water quality by providing aeration to maintain water health. Partners need a technological assistance that can improve the quality of results and production levels in a shorter time, and of course not incur large electricity costs from using this technology. This community service program activity is designed to solve partner problems. The proposal team provided a technology product called E-Ox Level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In this study, we compared different siphonation and aeration treatments in ponds A, B, C, and D. The results showed that the highest growth rate was pond "B" which was regularly aerated and siphoned. These results are also reinforced by similar research conducted by (Kusumah et al, 2021 andKusumah et al, 2022). This happens because DO levels are needed by fish organisms for metabolic processes, so the value changes quickly.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this study, we compared different siphonation and aeration treatments in ponds A, B, C, and D. The results showed that the highest growth rate was pond "B" which was regularly aerated and siphoned. These results are also reinforced by similar research conducted by (Kusumah et al, 2021 andKusumah et al, 2022). This happens because DO levels are needed by fish organisms for metabolic processes, so the value changes quickly.…”
Section: Introductionsupporting
confidence: 66%
“…Figure 1 Illustration of data collection observations (Kusumah et al, 2021;Kusumah et al, 2022;Siskandar et al, 2022)…”
Section: © Copyright By Indonesian Aquaculture Society 2023mentioning
confidence: 99%
“…Kualitas suatu perairan merupakan syarat penting yang dapat mempengaruhi kelangsungan hidup perkembangan, pertumbuhan, dan tingkat produksi ikan. Hal dasar yang menyebabkan gagal panen dalam usaha budidaya ikan lele adalah cuaca, pemahaman teknik yang masih minim dan kualitas air yang buruk (Kusumah et al, 2021). Dengan kualitas air yang baik, maka perkembangan dari ikan pun akan semakin baik pula dan tidak akan mengalami gangguan perkembangan.…”
Section: Pendahuluanunclassified
“…Penelitian dan pengembangan lebih lanjut dalam bidang ini akan terus menghasilkan inovasi-inovasi baru yang dapat meningkatkan efisiensi dan efektivitas dalam budidaya ikan, serta memberikan kontribusi yang berarti dalam menjaga kesehatan lingkungan perairan. Salah satu inovasi lainnya yaitu pada penelitian yang dilakukan oleh (Kusumah et al, 2021) yang menerapkan teknologi E-Ox Level pada kolam budidaya ikan lele dengan menghasilkan nilai yang posistif. Keunggulan dari E-Ox Level adalah menggunakan energi matahari sebagai pembangkit tenaganya (Kusumah et al, 2022).…”
Section: Gambar 7 Membership Function Editorunclassified
“…The LCD displays information in a clear and accessible manner, offering a user-friendly interface for operators to monitor the real-time counting results (Kusumah et al 2021). It plays a crucial role in presenting the output data, such as daily, weekly, and monthly counts, allowing users to quickly and easily access relevant information without the need for additional devices ).…”
Section: Introductionmentioning
confidence: 99%